DO GREEN BONDS DELIVER BETTER FINANCIAL PERFORMANCE? EVIDENCE FROM DUPONT ANALYSIS - Nilawati Nilawati; Mira Mira; Muhammad Khaedar Sahib (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Increased attention to environmental issues has driven the development of sustainable financing instruments, one of which is Green Bonds, although corporate participation in Indonesia is still relatively limited. This study aims to compare the financial performance of companies issuing Green Bonds and Conventional Bonds and to examine the relationship of DuPont components to Return on Equity (ROE). This study uses a descriptive quantitative method with secondary data from financial statements and banking bonds for the 2022–2024 period. Analysis was performed using the DuPont approach to break down the components forming ROE. The results show that companies issuing Green Bonds have a higher average ROE compared to Conventional Bond issuers. Asset Turnover shows a significant relationship with ROE for Green Bond issuers, while for Conventional Bond issuers, Asset Turnover and Operating Profit Margin show a significant relationship. These findings indicate that efficiency in asset utilization is a key characteristic in banking financial performance.